2023
DOI: 10.1038/s41598-023-40856-5
|View full text |Cite
|
Sign up to set email alerts
|

Co-use of MDMA with psilocybin/LSD may buffer against challenging experiences and enhance positive experiences

Richard J. Zeifman,
Hannes Kettner,
Broc A. Pagni
et al.

Abstract: Psilocybin and lysergic acid diethylamide (LSD) experiences can range from very positive to highly challenging (e.g., fear, grief, and paranoia). These challenging experiences contribute to hesitancy toward psychedelic-assisted psychotherapy among health care providers and patients. Co-use of 3,4-Methylenedioxy methamphetamine (MDMA) with psilocybin/LSD anecdotally reduces challenging experiences and enhances positive experiences associated with psilocybin/LSD. However, limited research has investigated the ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 84 publications
0
7
0
Order By: Relevance
“…Looking ahead, increasing clinical interest is being placed on the biased 5-HT1a agonist psychedelic 5-MeO-DMT (Dourron et al, 2023), a substance which is capable of inducing powerful and long-lasting antidepressant effects in minutes (Uthaug et al, 2019). Clinical attention is also beginning to be paid to the positive effects of co-administration of MDMA along with LSD or psilocybin (Straumann et al, 2023; Zeifman, Kettner, et al, 2023), a combination which may also result in a net 5-HT1a agonism bias and greater tolerability (Schechter, 1998). Rather than focusing on the development of non-hallucinogenic psychedelics, which may prove to have limited efficacy outside of animal models (Yaden & Griffiths, 2020), significant evidence exists in support of exploring the pharmacological design space of psychedelic substances with a biased 5-HT1a binding profile similar to that of 5-MeO-DMT or LSD co-administered with MDMA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Looking ahead, increasing clinical interest is being placed on the biased 5-HT1a agonist psychedelic 5-MeO-DMT (Dourron et al, 2023), a substance which is capable of inducing powerful and long-lasting antidepressant effects in minutes (Uthaug et al, 2019). Clinical attention is also beginning to be paid to the positive effects of co-administration of MDMA along with LSD or psilocybin (Straumann et al, 2023; Zeifman, Kettner, et al, 2023), a combination which may also result in a net 5-HT1a agonism bias and greater tolerability (Schechter, 1998). Rather than focusing on the development of non-hallucinogenic psychedelics, which may prove to have limited efficacy outside of animal models (Yaden & Griffiths, 2020), significant evidence exists in support of exploring the pharmacological design space of psychedelic substances with a biased 5-HT1a binding profile similar to that of 5-MeO-DMT or LSD co-administered with MDMA.…”
Section: Discussionmentioning
confidence: 99%
“…There is also a research literature on the anxiolytic effects of biased 5-HT1a agonists, such as 8-OH-DPAT, in rodent models of psychopathology (Luscombe, Martin, Hutchins, Gosden, & Heal, 1993; Schreiber & De Vry, 1993), and these effects are consistent with those of MDMA and other 5-HT releasing drugs. Reductions in anxiety and avoidance are key mediators in a variety of common psychopathologies and their treatment by psychedelic therapy (Zeifman, Wagner, Monson, & Carhart-Harris, 2023), suggesting a potential link between these effects and 5-HT1a agonism. Notably, outcomes from MDMA assisted therapy are characterized by a significant acute decrease in experiential avoidance (Mitchell et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…I think LSD and psilocybin are potent tools for reducing resistance. Mixing LSD or psilocybin with MDMA is widely practiced, though poorly studied [171]. We suggest starting with very low doses because LSD or psilocybin-assisted psychotherapy are known for deeply challenging experiences.…”
Section: Resistance or Distractionmentioning
confidence: 99%
“…This combination is common practice in MDMA-therapy, but no studies have been done [28]. Acutely safe co-use is known from recreational contexts [171].…”
Section: Resistance or Distractionmentioning
confidence: 99%
“…In a pilot study, 20 patients with life-threatening illnesses received MDMA with two psychotherapy sessions resulted in a significant reduction in trait anxiety compared to placebo in patients with anxiety secondary to a life-threatening illness, with results remaining stable after 6 months and 1 year ( 14 ). Moreover, a recent survey study with 27 respondents has shown that co-use of 3,4-Methylenedioxy methamphetamine (MDMA) with psilocybin/LSD anecdotally reduces challenging experiences such as anxiety and fear, while enhancing positive experiences such as self-compassion and gratitude associated with psilocybin/LSD use ( 15 ). These survey results were limited by use of convenience sample and small sample size.…”
Section: Introductionmentioning
confidence: 99%